The war calendar of the general levy of nobility in the times of Władysław Jagiełło - Grabarczyk, Tadeusz (Armia kontra natura, 2020)
This article concerns the participation of knights in wars during the reign of Władysław Jagiełło (1386–1434). Its goal is to determine how often and for how long the king called up the army, which will allow to assess how absorbing war expeditions were for knights at that time. The analysis shows that the king called knights 22 times minimum, of which the army from all over the Kingdom of Poland (expeditio generalis) was issued seven times, the remaining mobilizations concerned knights from one province (expeditio particularis). In addition, there were also smaller-scale defensive clashes, mainly near the Polish borders with the Teutonic Order and Silesia (defensio terrae). From the announcement of mobilization to the gathering of troops, it took from 2 to 8 weeks, this time depended on whether the expedition from one province or the whole Kingdom was convened. Preparations for the latter took longer, because the knights needed more time to get to the place of concentration of troops. In the case of local activities, the fighting was carried out for 2–4 weeks, in the case of expeditio generalis the campaigns lasted 8–13 weeks. During the most intense war period of 1409–1422, knights were called up to eight times. Participation in wars was absorbing for knights. Most of the conflicts took place in the summer, which forced the nobility to leave their farms at harvest time. Participation in the wars was costly, and the king refused to pay any remuneration for participating in the expedition abroad, despite his commitment to do so in 1388. Starting from 1419, the deterioration of the relationship between the king and the knights during expeditions can be seen. Worsening of discipline in the army becomes apparent.